Microthermal Damage of Granite in Gonghe Basin, Qinghai Province - XIE Jin; XI Baoping; HE Shuixin; LI Xiaoke; CAI Jiahao; JIA Peng (Taiyuan Ligong Daxue xuebao)
[Purposes] Granite is one of the main rock masses for geothermal energy storage in dry hot rocks. Studying the damage mechanism of granite caused by heat and thermal shock has certain engineering and theoretical significance for geothermal exploitation in dry hot rocks. [Methods] The entire process of slowly raising granite from room temperature to 600 ℃, natural cooling in air or thermal shock cooling in water to room temperature was observed by using a polarizing microscope. The microscopic structures were analyzed by quantitatively analyzing the mineral area and the number of cracks in the field of view to investigate the damage effects on granite during the heating process and after thermal shock in different cooling media. [Findings] The results indicate that: 1) The mineral area of granite increases with temperature rise during the heating process. After natural cooling from high temperature, the mineral area is slightly larger than that before heat treatment, while after thermal shock in water, the mineral area is slightly smaller than that at 600 ℃ but significantly larger than that before the heat treatment.2) During the heating process, the overall trend of cracks in the field of view shows an increase in small cracks, followed by the formation of large cracks through the penetration of small cracks, and a continuous increase in both large and small cracks. The critical temperature for a decrease in small cracks and an increase in large cracks is around 300 ℃.3) After thermal shock in water, the total number of cracks in the high-temperature granite increases, with a significant increase in cracks between 0−100 μm. In contrast, after natural cooling in air, the total number of cracks in the granite decreases, and there is a significant decrease in cracks between 0−100 μm. This indicates that shorter and smaller cracks are more sensitive to cooling processes. 4) Through analyses of the mineral contraction degree and cracks amount changes, it is found that internal fracturing of high-temperature granite caused by thermal shock cooling in water is more severe.